PTH-183 Upper gastrointestinal cancer red flag symptoms alone except dysphagia do not predict the presence of upper gastrointestinal tract cancer: implications for practice. (22nd June 2015) - Sultan, S; Shandro, BM; Friday, S; Wang, B; Suleman, M; Cooney, J; Paskaran, P; Gupta, S; Mendall, M
Abstract : Introduction: The epidemiology of upper gastrointestinal (UGI) cancer is rapidly changing. Current guidelines for red flag symptoms for UGI cancer were drawn up using evidence from a past age. With the exception of dysphagia, many of the symptoms are non-specific for UGI cancer in particular dyspepsia, particularly with the rapidly declining prevalence of H. pylori and its associated gastric cancers. Aims: To determine the value of individual UGI cancer red flag symptoms alone or in combination in predicting the presence of UGI and non-UGI cancers. Method: Our routine practice is to investigate all patients referred under the urgent suspected cancer (USC) pathway with an oesophagogastroduodenoscopy (OGD) and a computed tomography (CT) scan if over 50 years of age and symptoms are not purely oesophageal. A retrospective case review between October 2013 to March 2014 of all referrals on the USC pathway to our district general hospital with a case review of all the UGI cancers detected by our service over a one year period (October 2013–2014). Clinical follow-up after referral was a minimum of 11 months. Results: 391 patients (20–96 age range) were seen under the USC pathway between October 2013–March 2014. In total 372 and 177 patients were investigated with an OGD and a CT scan respectively; 289 and 161 respectively were patients over the age of 50. 19 cancers were detected giving a detection rate of 4.75%. Of those only nine were UGI cancers (three gastric, six oesophageal). Other cancers found included three colorectal, one pancreatic, three lung, one cholangiocarcinoma, one ovarian and one peritoneal. The table shows the symptoms distribution for both UGI and non-UGI cancers. Isolated red flag symptoms had poor predictive power. Weight loss and dysphagia in combination with other symptoms had the best predictive value. There was a similar number of UGI cancers (23) and non UGI cancers (19). Analysis of all UGI cancers n = 47 over the course of one year not necessarily presenting through the USC route (October 2013–2014) revealed that isolated dyspepsia was found in only two of 47 patients compared to iron deficiency anaemia, weight loss and dysphagia which were the sole presenting symptoms in seven, four and three patients respectively, reinforcing the findings from the USC referrals. Conclusion: In modern times, isolated UGI cancer red flag symptoms particularly dyspepsia are poorly predictive of UGI cancer, and equally well predict the presence of cancer outside the UGI tract. CT scanning should be a routine part of evaluation of UGI cancer referrals in the over 50's. Disclosure of interest: None Declared.